Belanja Kesehatan Pemerintah dan Penurunan Prevalensi Stunting di Indonesia - Diena Tiara Sari (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
Indonesia has started to set policies and programs to alleviate stunting prevalence in the last decade. By reducing stunting prevalence, the government has cut the short-term and long-term effects of stunting. Government health expenditure at the regional level is also part of regional government expenditure, which is proposed to overcome health issues. This research empirically examines the correlation between government health expenditure and stunting prevalence reduction in Indonesia. The data on government health expenditure is obtained from the Ministry of Finance, and the data on stunting prevalence is compiled from several sources such as Riskesdas (Ministry of Health), SSGBI (Ministry of Health), and Statistics of Indonesia (BPS). The panel data uses the provincial level of data from 2010 until 2020, covering 33 provinces, and is estimated with the Fixed Effects (FE) model and the robustness check of the heteroskedasticity problem using fixed robustness. The results show that government health expenditure significantly reduces the prevalence of stunting in all provinces and provinces located outside Java Island.